Pengaruh Model Pembelajaran Kooperatif Tipe Student Teams Achievement Devisions (STAD) Terhadap Kemampuan Pemecahan Masalah Matematis Siswa pada Materi Relasi dan Fungsi di SMP Swasta Taman Siswa Pematangsiantar - Tanjung, Sahima Rosana; Sidabutar, Ropinus; Tambunan, Lois Oinike (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of the Student Teams Achievement Divisions (STAD) cooperative learning model on the mathematical problem-solving abilities of eighth-grade students in the Relations and Functions subject at Taman Siswa Pematangsiantar Private Junior High School in the 2025/2026 academic year. The research method used was a quantitative approach with regression analysis techniques. The results showed that the STAD learning model had a positive and significant effect on students' mathematical problem-solving abilities. This was demonstrated by the regression equation Ŷ = -36.516 + 2.291X with a regression coefficient value of 2.291. In addition, the coefficient of determination value of 89.3% indicates that the STAD learning model variable contributes strongly to improving students' mathematical problem-solving abilities. Thus, the application of the STAD cooperative learning model can be used as an alternative learning strategy to improve students' mathematical problem-solving abilities in relations and functions.